Il BIM: nuovo modello imperativo per i rilievi Palazzo San Giorgio di Genova l'antichití al pass o con la nuova era digitale - Maria Chiara Spezia (mediaGEO soc. coop., 2020)
The new relevant technologies applied to cultural heritage - in particular the application of the BIM methodology - allow to better understand the impacts of detailed planning. Geomar, a competent company in architectural and topographical surveys, testifies how a cutting-edge survey can make the dissemination of built heritage ever easier.